TEACHER METHOD PATTERNS TO STRENGTHEN THE ABILITY TO READ THE KORAN IN PUBLIC EDUCATIONAL INSTITUTIONS - Ziaulhaq, Wahyu (JURNAL EKONOMI AKUNTANSI MANAJEMEN AGRIBISNIS, 2023)
This study describes the teacher's strategy to strengthen the ability to read the Koran to students in public schools. In accordance with the desired focus, the answer was found through research, a qualitative approach to the research subject was used as class V students and research informants were PAI teachers and schools. Data obtained through interview and observation techniques so that the following conclusions are obtained: The role that has been done by the PAI teacher is very helpful for students in learning to read the Qur'an. The PAI teacher has succeeded in helping students from those who do not understand or even do not know the letters of Hijayyah to understand and begin to recognize the hijayyah letters even though there are obstacles that arise from within the students and the fossility possessed by the school. The obstacle is, the room facility is still very simple